Hepatic myomatous angiomyolipoma diagnosedpreoperatively from specific imaging features: A case report. (2018) - Sakuraoka, Yuhki; Suzuki, Takashi; Tanaka, Gennki; Shimizu, Takayuki; Shiraki, Takayuki; Kyongha, Park; Mori, Shozo; Iso, Yukihiro; Kato, Masato; Aoki, Taku; Kubota, Keiichi; Yamagishi, Hidetsugu; et al.
Highlights: An extremely rare case report of hepatic myomatous angiomyolipoma. Including specific imaging features to diagnose with hepatic angiomyolipoma. There is a significant interesting imaging findings of hepatic myomatous angiomyolipoma. Previous reports only revealed the pathological findings and a few imaging findings, however we show two specific features of imaging with rare pathological findings. Abstract: Introduction: Hepatic angiomyolipoma is a rare tumour and is difficult to obtain the accurate diagnosis preoperatively because the imaging features are similar to hepatocellular carcinoma. Presentation of Case: We present a case study of an 80-year old woman with a liver tumour measuring 6.2 cm × 6.0 cm. We were able to diagnose the tumour preoperatively as a rare hepatic myomatous angiomyolipoma based on the presence of early venous return evident on angiography and small low-intensity areas corresponding to fat within the tumour revealed by out-of-phase EOB-MRI. The tumour was removed by minimally invasive surgery and our preoperative diagnosis was confirmed by positive immunoreactivity for both angiomyolipoma-specific human melanoma black 45 and smooth muscle cell positivity for melanin. Discussion: We consider that the information obtained in this case will be useful for preoperative diagnosis of other hepatic angiomyolipomas, thus facilitating more appropriate and less invasive surgery and improving the overall outcome. Conclusion: Hepatic myomatous angiomyolipoma is a rare tumour. We illustrated the two specific imaging features to diagnose it preoperatively.